2006
DOI: 10.1038/sj.eye.6702126
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant topical mitomycin C chemotherapy for conjunctival and corneal intraepithelial neoplasia

Abstract: References

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…[345] Topical chemotherapy with mitomycin-C (MMC), cidofovir, 5-fluorouracil (5-FU), or immunotherapy with interferon alpha 2b (INF α2b) has been found to be effective in the treatment of noninvasive OSSN. [67891011]…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[345] Topical chemotherapy with mitomycin-C (MMC), cidofovir, 5-fluorouracil (5-FU), or immunotherapy with interferon alpha 2b (INF α2b) has been found to be effective in the treatment of noninvasive OSSN. [67891011]…”
mentioning
confidence: 99%
“…Topical agents offer the advantage of delivering treatment not only to the affected ocular surface but also to the entire ocular surface, and thus potentially eliminating subclinical OSSN, and also diminish the risk of limbal stem cell deficiency and associated ocular surface morbidity. [678910111213141516171819202122] Although the efficacy of topical medications on OSSN is comparable (80%–100%),[678910111213141516171819202122] MMC has the highest reported rates of side effects (76%), followed by 5-FU (42%), and INF α2b is reported to have the least rates of side effects (15%). [1819] However, the cost of INF α2b ($US 175–225 per treatment) could limit its use in some patients.…”
mentioning
confidence: 99%
“…Preoperative (neoadjuvant chemotherapy) application is with the intent of decreasing tumour size prior to definitive surgery 1 11. Intraoperative application is used as a substitute for cryotherapy.…”
mentioning
confidence: 99%
“…26 MMC may be stored at room temperature for up to 1 week and under refrigeration (41C) for up to 3 months, and still preserve its activity. [30][31][32][33][34][35][36][37][38][39][40][41] Several authors have reported the use of preoperative topical MMC in reducing the size of the epithelial tumor before excision, 42,43 or used it intraoperatively 44 (Fig. The use of topical MMC for CIN was first described by Frucht-Pery and colleagues as a sole treatment.…”
Section: MMCmentioning
confidence: 99%